2013
DOI: 10.1371/journal.pone.0069364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diurnal Fluctuating versus Constant Temperatures on Germination of 445 Species from the Eastern Tibet Plateau

Abstract: Germination response to fluctuating temperatures is a mechanism by which seeds detect gaps in vegetation canopies and depth of burial in soil, and it is very important for plants. Thus, studies on the effect of fluctuating temperature on germination at the community level are valuable for understanding community structure and biodiversity maintenance. We determined the effects of two alternating temperatures (5/25°C and 10/20°C) and one constant temperature (15°C) on seed germination of 445 species in a grassl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 31 publications
5
57
0
1
Order By: Relevance
“…(2013) found significant differences in daily temperature at different successional meadows during the growing season, with the lowest daily temperature of 5°C near the soil surface in early‐successional meadows and 10°C near the soil surface in late‐successional meadows. They also found that the daily temperature range was ~5–25°C near the soil surface in early‐successional meadows and ~10–20°C near the soil surface under vegetation in late‐successional meadows.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2013) found significant differences in daily temperature at different successional meadows during the growing season, with the lowest daily temperature of 5°C near the soil surface in early‐successional meadows and 10°C near the soil surface in late‐successional meadows. They also found that the daily temperature range was ~5–25°C near the soil surface in early‐successional meadows and ~10–20°C near the soil surface under vegetation in late‐successional meadows.…”
Section: Discussionmentioning
confidence: 99%
“…Early‐successional communities tend to be dominated by life forms such as forbs that are annual plants and good colonist, whereas older meadows are increasingly dominated by graminoids that are mostly perennial and good resource competitors (Liu et al., 2013; Zhang et al., 2015). Thus, colonists (forbs) such as Geranium phlzowianum and Potentilla ansrina are abundant across early stages at both sites, while competitors (graminoids) dominate at later stages include Elymus nutans Griseb and Kobresia pygmaea (C. B. Clarke ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations